2013
DOI: 10.31018/jans.v5i2.349
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a bacterial collar and rhizome rot of banana (Musa paradisiaca) caused by strains of Erwinia chrysanthemi pv. paradisiaca

Abstract: A serious collar and rhizome rot disease of banana was observed in the north region of Maharashtra state in post rainy season. The disease was caused by the bacterial strains of Erwinia chrysanthemi pv. paradisiaca identified and characterized by morphological, physiological, biochemical and pathogenicity tests. The infection occurred on new banana plantation of one month old in poorly drained soil. In post rainy season, banana plantations of 8 to 10 weeks were found severely infected. E. chrysanthemi pv. para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
3
3
0
Order By: Relevance
“…An inhibition zone was observed around the filter paper disc containing streptomycin solution whereas no inhibition zone was observed around the filter paper disc containing erythromycin. P. carotovorum is reported to be resistant to erythromycin and susceptible to streptomycin (Dickey and Victoria, 1980;Snehalatharani and Khan, 2010;Nagrale et al, 2013;Akbar et al, 2015). Since the isolates in this study are resistant to erythromycin and susceptibility to streptomycin, it is confirmed that they belong to Pectobacterium carotovorum.…”
Section: Kbsupporting
confidence: 71%
See 1 more Smart Citation
“…An inhibition zone was observed around the filter paper disc containing streptomycin solution whereas no inhibition zone was observed around the filter paper disc containing erythromycin. P. carotovorum is reported to be resistant to erythromycin and susceptible to streptomycin (Dickey and Victoria, 1980;Snehalatharani and Khan, 2010;Nagrale et al, 2013;Akbar et al, 2015). Since the isolates in this study are resistant to erythromycin and susceptibility to streptomycin, it is confirmed that they belong to Pectobacterium carotovorum.…”
Section: Kbsupporting
confidence: 71%
“…Deteriorating of the pseudostem has started and finally the plant chop down as the pseudostem got entirely rotten and emitted foul smell, after 16 days of inoculation. Nagaraj et al, (2012) and Nagrale et al, (2013) reported that complete rotting of healthy rhizome bits were observed after 37 DAI under in vivo condition. The similar plant symptoms were observed by Thomas et al, (2008) who demonstrated that plants inoculated with pathogenic Pectobacterium carotovorum subsp.…”
Section: Pathogenicity and Virulence Testmentioning
confidence: 99%
“…The coloration occurs as a result of reductive deamination of tryptophan by the action of tryptophanases (Schaad et al, 2001), which confirms that these isolates belong to the species D. chrysanthemi. These results agree with those of Nagrale et al (2013) for E. chrysanthemi pv. paradisiaca, Ashmawy et al (2015), Bhupendra and Yogendra (2015), and Vasundhara and Thammaiah (2017), who observed that D. chrysanthemi caused production of indole acid when performing this biochemical test to characterize bacterial isolates.…”
Section: A B Csupporting
confidence: 91%
“…Colonies of D. chrysanthemi, D. paradisiaca and P. carotovorum subsp. carotovorum were isolated from different crops, including bananas using NA culture medium, with similar results to those obtained in the present work (Nagrale et al, 2013;Akbar et al, 2015;Czajkowski et al, 2015;Vasundhara and Thammaiah, 2017).…”
Section: A B Csupporting
confidence: 90%
See 1 more Smart Citation